2008
DOI: 10.1002/pc.20412
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polystyrene/clay nanocomposite by suspension and emulsion polymerization

Abstract: Organophilic montmorillonite was prepared using ion‐exchange method between sodium ions in clay layers and four kind of quaternary ammonium salt. The montmorillonite has the largest d001‐spacing, as determined by X‐ray diffraction in modified by di(hydrogenated tallowalkyl) dimethyl ammonium chloride. Polystyrene montmorillonite nanocomposites were obtained by suspension and emulsion polymerization of styrene in the dispersed organophilic montmorillonite. The d001‐spacing of clay was determined by X‐ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…By increasing clay loading, the temperature at which degradation of nanocomposites takes place rises. The degradation temperature is increased by adding nanoclay content because clay platelets can retard heat transfer in the matrix and also strengthen the polymer chains to avoid heat degradation [45] . Additionally, the hindrance effect of nanoplatelets on the polymer chains motion, interaction between clay platelets and polymer matrix, and restriction of oxygen permeation by silicate sheets, are other reasonable explanations for increasing the degradation temperature of the nanocomposites [11,46,47] .…”
Section: Psmentioning
confidence: 99%
“…By increasing clay loading, the temperature at which degradation of nanocomposites takes place rises. The degradation temperature is increased by adding nanoclay content because clay platelets can retard heat transfer in the matrix and also strengthen the polymer chains to avoid heat degradation [45] . Additionally, the hindrance effect of nanoplatelets on the polymer chains motion, interaction between clay platelets and polymer matrix, and restriction of oxygen permeation by silicate sheets, are other reasonable explanations for increasing the degradation temperature of the nanocomposites [11,46,47] .…”
Section: Psmentioning
confidence: 99%
“…Wang et al observed that ultrasound or ultrasonic irradiation processes assisted emulsion polymerization and could promote the formation of exfoliated layers during nanocomposite synthesis [28]. In addition, the results of Yang et al indicated that PS-clay nanocomposites synthesized via emulsion polymerization had better layer dispersion than those synthesized by suspension polymerization [29]. Therefore, emulsion polymerization is an efficient technique for preparing polymer-MMT nanocomposite particles with exfoliated structures and monodispersity.…”
Section: Introductionmentioning
confidence: 99%
“…So many open papers have reported polystyrene (PS)/inorganic particles composites. Yang et al have synthesized PS/clay nanocomposite by suspension and emulsion polymerization . Yang et al have successfully prepared PS/montmorillonite nanocomposite via in situ emulsion polymerization .…”
Section: Introductionmentioning
confidence: 99%